Three sisters, three queens - Gregory, Philippa (New York : Touchstone, 2016)
Brought to the Tudor court as a young bride, Katherine of Aragon forges a unique sisterhood with the king's sisters, Margaret and Mary, that is shaped by rivalries, wars, betrayal, widowhood, motherhood, passion, and secrets.
Keywords: Catharine, -- of Aragon, Queen, consort of Henry VIII, King of England, -- 1485-1536 -- Fiction; Margaret, -- Queen, consort of James IV, King of Scotland, -- 1489-1541 -- Fiction; Mary, -- Queen, consort of Louis XII, King of France, -- 1496-1533 -- Fiction; Great Britain -- History -- Tudors, 1485-1603 -- Fiction; Biographical fiction; Historical fiction